Design and Implementation of PID Controller for Phase Shifted Full Bridge DC-DC Converter - Ibrahim, Luay G.; Shneen, Salam Waley (Buletin Ilmiah Sarjana Teknik Elektro, 2025)
The study aims to evaluate the converter's operation and how to improve it, and to discuss the performance and behavior of the system in transient and steady states. Phase shifted full bridge DC-DC Converter (PSFB), converter is one of the most popular isolated converter, which is widely used in many applications. So today we are discussing its working, design and MATLAB simulation. converters are used frequently to step down high dc voltages to lower voltages. It also provides isolation between input and output stages. it is major application includes, server power supply, telecom rectifier, battery charging system and renewable energy systems. This is the basic structure of a full bridge DC-DC Converter. we have a dc voltage source at the input. there are the power electronic switches, which can be either MOSFET or IGBT. this is a high frequency transformer. used for the isolation between input and output stages. it also provides the required voltage gain. an inductor is used to limit the output current ripple, and a capacitor used as the filter to regulate the output voltage. To meet the necessary demand, in addition to regulating the quality of electrical power to address the changes and fluctuations in the system caused by various factors, the output of the converters is enhanced by developing a model design through simulation to provide the appropriate voltage, current, and power to cover the required load. Industrial applications are among the most important industries that employ and use electronic power converters, including the DC-DC converter, especially the PSFB. Among these applications are charging systems for storage units in electricity generation systems from renewable energies, including solar or wind energy, with a DC generator. It can also be part of a lighting system or microgrids, as this converter is characterized by high efficiency in performance, quality, and reliability, and has the advantage of a wide range at high frequencies. The PSFB converter consists of a DC source to supply a DC load, connected to an inverter on the source side and a filter on the load side, with a rectifier between them. The rectifier is a bridge type of four diodes, the inverter is a bridge of four MOSFET transistors, and the LC filter consists of a coil and a capacitor. Among the areas that require a wide frequency range are communications systems, which is one of the most important applications and areas of use for this converter.